Aluno com deficiência intelectual no atendimento educacional especializado em Matemática - Patrício, Maria Aparecida Marcelino (2020)
This research has as a main objective to investigate inclusive pedagogical practices that mediate the teaching-learning process of mathematical contents, beside students with intellectual disabilities who receive Specialized Educational Assistance (SEA) offered in the Multifunctional Resource Rooms, at public schools in the municipality of Queimadas, Paraíba, Brazil. Referring to the methodology, a descriptive research was carried out with a qualitative approach, with the semi-structured interview and the documentary analysis as instruments for data collection. This interview was applied with five teachers who worked in the SEA rooms, from August to October 2018. The interview was divided into two sections, the first to collect personal and professional data and the second to collect data related to the teaching- learning process of students with intellectual disabilities in mathematics. The documentary analysis is based on the analysis carried out in the SEA Plans prepared by the teachers that participated in the present research. The results of the interviews indicated that the difficulties encountered by SAE teachers in promoting meetings with teachers of regular classes end up compromising the pedagogical practices of mathematics in the common classroom. Regarding the use of pedagogical resources in the teaching-learning process of mathematical content, the research participants reported that they make use of several manual and digital resources, including in the assessment of learning. Regarding the analysis of SEA Plans, we found that the collaborators in the present research demonstrate difficulties in defining resources that would be applied and elaborating the activities, as well as aligning the objectives with the goals foreseen in the student's teaching-learning process with intellectual disability. We conclude the importance of reinforcing the need to better invest in continuous training for SEA teachers, so that they become multipliers of actions in the school space, based on the realization of plans in conjunction with teachers in the common classroom.